Antarctic cyanobacterium Nostoc CCC537, a new source of Î³-linolenic acid and its antibacterial potential - Verma, Deepali; Asthana, Ravi Kumar; Nath, Gopal (Chemical Biology Letters, 2021)
Unsaturated fatty acids are one of an important component of our healthy diet as needed for various physiological functions as well as it has medicinal significance. The Gamma linolenic acid (GLA), the pharmaceutically important fatty acid, was isolated from the Antarctic cyanobacetrium, NostocCCC537. The antibacterial potential of GLA was evaluated against Staphylococcus aureus ATCC25923, Pseudomonas aeruginosa ATCC27853, Salmonella typhi MTCC3216, Escherichia coli ATCC25992 and Enterobacter aerogenes MTCC2822. It was observed that GLA production in the cyanobacterium was also regulated by alterations in phosphate or nitrate levels during growth along with temperature. A doubling in the phosphate concentration (116 Î¼M) over that routinely used (58 Î¼M) in the diazotrophic medium, enhanced GLA production 20.5%, while the biomass yield decreased to 7.3% of the control. GLA production, however, decreased to 18% or 23% in 5 mM or 10 mM nitrate, respectively. A downshift in growth temperature to 10oC from 20oC enhanced GLA production. It is suggested that the Antarctic cyanobacterium may also act as a source of an antibacterial agent as well as GLA.